واقع استخدام تطبيقات الذكاء الاصطناعي في التصميم التعليمي وعلاقته ببعض المتغيرات الديموغرافية لدى أخصائي مصادر التعلم في مدارس محافظة ظفار - السعيدي، منذر بن خالد مرهون; العامري، سالم عبدالله; المهري، بخيت بن أحمد (المعهد العالي للدراسات النوعية, 2024)
هدفت الدراسة الحالية إلى التعرف على واقع استخدام تطبيقات الذكاء الاصطناعي في التصميم التعليمي لدى أخصائيو مصادر التعلم في علاقته ببعض المتغيرات الديموغرافية في مدارس محافظة ظفار. تمثلت عينة الدراسة الحالية في (73) أخصائي/ أخصائية مصادر تعلم من العاملين في المدارس الحكومية والخاصة في مدارس محافظة ظفار. تكونت أداة الدراسة من مقياس استخدام تطبيقات الذكاء الاصطناعي في التعليم النفسي من إعداد الباحثين. وقد تم استخدام الأساليب الإحصائية التالية: المتوسطات الحسابية والانحرافات المعيارية اختبار ت، وتحليل التباين الأحادي، ومعامل ارتباط بيرسون. توصلت الدراسة إلى وجود أن استخدام تطبيقات الذكاء الاصطناعي في التصميم التعليمي لدى أخصائيو / أخصائيات مصادر التعلم في محافظة ظفار عند مستوى عال. كما بينت الدراسة وجود فروق دالة إحصائية في استخدام تطبيقات الذكاء الاصطناعي في التصميم التعليمي لدى أخصائي مصادر التعلم في مدارس محافظة ظفار ولصالح الإناث. عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) على مقياس استخدام تطبيقات الذكاء الاصطناعي في سار التصميم التعليمي لدى أخصائي/ أخصائية مصادر التعلم في مدارس محافظة ظفار تعزى لمتغير المدرسة. كما بينت الدراسة عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.05) في استخدام تطبيقات الذكاء الاصطناعي في التصميم التعليمي تعزى لمتغير سنوات الخبرة. إضافة إلى عدم وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0,05) في استخدام تطبيقات الذكاء الاصطناعي في التصميم التعليمي لدى أخصائيو مصادر التعلم في مدارس محافظة ظفار تعزى لمتغير التخصص الدراسي. The current study aimed to identify the reality of the use of artificial intelligence applications in educational design by learning resource specialists in its relationship to some demographic variables in schools in Dhofar Governorate. The sample of the current study consisted of (73) learning resources specialists working in public and private schools in the schools of Dhofar Governorate. The study tool consisted of a measure of the use of artificial intelligence applications in psychological education prepared by researchers. The following statistical methods were used: arithmetic means and standard deviations, t-test, one-way analysis of variance, and Pearson correlation coefficient The study found that the use of artificial intelligence applications in educational design among learning resource specialists in Dhofar Governorate is at a high level. The study also showed that there are statistically significant differences in the use of artificial intelligence applications in educational design among learning resources specialists in schools in Dhofar Governorate, in favor of females. There are no statistically significant differences at the significance level (0.05) on the scale of the use of artificial intelligence applications in educational design among the learning resources specialist in the schools of Dhofar Governorate due to the school variable. The study also showed that there are no statistically significant differences at the significance level (0.05) in the use of artificial intelligence applications in educational design due to the years of experience variable. In addition, there are no statistically significant differences at the significance level (0.05) in the use of artificial intelligence applications in educational design among learning resource specialists in schools in Dhofar Governorate due to the academic specialization variable.
Keywords: العملية التعليمية -- الذكاء الاصطناعي -- التصميم التعليمي -- سلطنة عمان